A Graceful EXIT impeded by obstetrical complications. Issue 2 (5th February 2021) - Zaretsky, Michael; Brockel, Megan; Derderian, Sarkis Christopher; Francom, Christian; Wood, Cristina
Abstract : We report an ex utero intrapartum therapy-to-airway procedure in which obstetric factors dramatically influenced the sequence of events necessary to complete the procedure.